2011
DOI: 10.2478/v10078-011-0048-3
|View full text |Cite
|
Sign up to set email alerts
|

Retesting The Validity Of A Specific Field Test For Judo Training

Abstract: The main goal of this research project was to retest the validity of a specifically designed judo field test (Santos Test) in a different group of judokas. Eight (n=8) national-level male judokas underwent laboratory and field testing. The mean data (mean +/− SD) obtained in the laboratory tests was: HRmax: 200 ± 4.0 beats × min−1, VO2 max: 52.8 ± 7.9 ± ml × kg−1 × min−1, lactate max: 12 ± 2.5 mmol × l−1, HR at the anaerobic threshold: 174.2 ± 9.4 beats × min−1, percentage of maximum heart rate at which the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…The anaerobic threshold (%VO2max), which was measured in six individual studies (Callister et al, 1991; Ebine et al, 1991; Kim et al, 1996; Little, 1991; Santos et al, 2011; Santos et al, 2012; Sbriccoli et al, 2007), did not differ between male (77.2%, CL = 76.98; 77.48%) and female (76.6%, CL = 76.00; 77.26%) judo athletes.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The anaerobic threshold (%VO2max), which was measured in six individual studies (Callister et al, 1991; Ebine et al, 1991; Kim et al, 1996; Little, 1991; Santos et al, 2011; Santos et al, 2012; Sbriccoli et al, 2007), did not differ between male (77.2%, CL = 76.98; 77.48%) and female (76.6%, CL = 76.00; 77.26%) judo athletes.…”
Section: Resultsmentioning
confidence: 96%
“…Based on the available data, the body mass index (BMI) was calculated, with values from individual studies ranging from 23.3 to 33.6 kg·m -2 in men and from 21.6 to 25.6 kg·m -2 in women. In men, all the cohorts, except for Spanish athletes (Santos et al, 2011) were considered overweight compared to the international standard of BMI > 25 kg·m -2 (Cole et al, 2000), whereas among women, the overweight athletes were found only in the group of Koreans (Kim et al, 1996). Male body fat content (BF%) ranged from 8.3 to 14.5%, whereas in women, this value ranged from 12.4 to 20.6%, but was not reported in four samples.…”
Section: Resultsmentioning
confidence: 99%
“…Based on specific tasks, such as the number of repetitions obtained in the Santos Test, it is possible to prescribe exercises at the intensity of the anaerobic threshold or of the aerobic power, using variables as simple as HR and blood lactate concentrations. The test was initially designed for the assessment of high-level athletes 3 , but it has been observed that this test can be used in any competitive level 38 . Although the Santos Test presents characteristics from judo combats, such as intermittence and effort-pause relationship, it is necessary to carry out studies that ascertain if the energetic cost involved in the test is similar to that of a judo combat.…”
Section: Discussionmentioning
confidence: 99%
“…One weakness of the Santos Test is that the procedures are not presented in a totally clear manner, which can hamper the reproduction of the test by others researchers; for example, it is to understand what is performed during passive phase (moving on the tatami). Additionally, the indices presented in the two validation papers 3,38 generate some doubts regarding physical capacities to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…(TABBEN et al, 2014;BELTZ et al, 2016). Essa variável é facilmente mensurada por meio de um analisador de gases portátil (BELTZ et al, 2016), o qual oferece medidas de trocas gasosa em situação real (MCFARLANE;WONG, 2012;TABBEN et al, 2014) (AZEVEDO et al, 2007;AZEVEDO et al, 2014;SANTOS et al, 2010;SANTOS et al, 2011;SANTOS et al, 2012). Millet et al (2003), são variáveis muito importantes à serem avaliadas, para definir a estrutura do treinamento intermitente de alta intensidade.…”
Section: Reprodutibilidade Do Teste Progressivo Até a Exaustão De Uchunclassified